Computational Study of Quantum Coherence from Classical Nonlinear Compton Scattering with Strong Fields - Nieto-Chaupis, Huber (2022)
From the covariant formulation of radiation intensity of Hartemann-Kerman model entirely constructed in the classical electrodynamics scenario, a formulation of coherent states has been obtained in an explicit manner represented by the infinite sum of integer-order Bessel functions. Both linear and nonlinear Compton scattering are included, suggesting that Compton processes can be perceived as coherent states of lightmatter interaction.